Sustainability of Smart Ports: A Systematic Literature Review - Umut Dağıstan; Murat Atalay; Duygu Aydın Ünal; Sonay Zeki Aydın (SAGE Open)
As the global population continues to grow, and trade volumes increase, the demand for efficient and sustainable transportation infrastructure has become increasingly important. Notably, the role of smart ports in advancing sustainability has emerged as a critical concern. This study aims to provide a comprehensive systematic literature review (SLR) of smart port sustainability, capturing key research trends and proposing a research agenda based on an analysis of 68 peer-reviewed articles indexed in the Web of Science (WoS) between 2017 and 2023. In this respect, four themes were determined according to the thematic analysis. (1) Digital Transformation for Enhanced Efficiency and Sustainability; (2) Green Port Initiatives: Energy Efficiency and Renewable Energy Integration; (3) Smart Port Governance and Stakeholder Collaboration for Sustainable Development; (4) Challenges and Opportunities for Smart Port Sustainability. The findings reveal that while significant progress has been made in digitalization and environmental sustainability, gaps remain in balancing economic, social, and environmental dimensions. The study offers policymakers, port managers, and researchers recommendations to improve operatinonal efficiency, mitigate negative environmental effects, and promote inclusive governance. Future research could involve scaling digital solutions, furthering the maturity model, and other under-researched areas, including cybersecurity and financial incentives for sustainable technologies. By bridging these gaps, smart ports can evolve into resilient, future-ready ecosystems capable of thriving in an increasingly complex global maritime landscape.